Statin use associated with improved overall and cancer specific survival in patients with head and neck cancer. (March 2019) - Gupta, Abhinav; Stokes, William; Eguchi, Megan; Hararah, Mohammad; Amini, Arya; Mueller, Adam; Morgan, Rustain; Bradley, Cathy; Raben, David; McDermott, Jessica; Karam, Sana D
Highlights: A relationship between statins and improved outcomes in various cancers exists. We showed improved outcomes in head and neck cancer patients taking a statin. There was no statistically significant increase in toxicity. Abstract: Objectives: Studies have shown the utility of lipid-lowering agents in improving outcomes in various cancers. We aim to explore how statins affect overall survival and cancer specific survival in head and neck cancer patients using population-based datasets. Patients and methods: Using the Surveillance, Epidemiology, and End Results (SEER)-Medicare linked dataset, we separated HNC patients into three groups: those with no hyperlipidemia (nH), those with hyperlipidemia and not taking a statin (HnS), and those with hyperlipidemia and taking a statin (H + S). Overall survival (OS) and cancer specific survival (CSS) were compared between the three groups based on disease subsite (oral cavity, oropharynx, and other) using Kaplan-Meier and multivariate Cox regression analysis (MVA), controlling for demographic, socioeconomic, staging, treatment, and comorbidity covariates. Using Pearson chi-square analysis, we also compared the incidence of cancer-related toxicity events. Results: There were 495 nH, 567 HnS, and 530 H + S patients. H + S patients had superior OS and CSS (73.0, 81.2%) relative to nH (58.6, 69.1%) and HnS groups (61.7, 69.2%) (p < 0.01). On MVA, H + S patients showed improved OS (p < 0.01) and CSS (p = 0.04) compared to nH (HR = 1.64, 1.56) and HnS (HR = 1.40, 1.37). MVA stratified by subsite yielded similar results for oral cavity and oropharyngeal disease. Toxicity-related events did not differ significantly between the groups. Conclusion: HNC patients with hyperlipidemia and taking a statin demonstrated improved outcomes compared to nH and HnS patients, further supporting statins' role as a potential adjuvant anti-neoplastic agent in HNC. Further prospective studies to investigate the impact of statins on HNC outcomes are warranted.